Investigation of partial discharge characteristics in mineral oil induced by dibenzyl disulfide - Azis, Norhafiz; Mohd Selva, Amran; Tariq, Muhammad Umair; Ab Kadir, Mohd Zainal Abidin; Jasni, Jasronita; Zainuddin, Hidayat (Universiti Putra Malaysia Press, 2025)
In this paper, an experimental study is carried out to investigate the partial discharge (PD) characteristic based on phase-resolved partial discharge (PRPD) and partial discharge inception voltage (PDIV) in mineral oil (MO) in the presence of dibenzyl disulfide (DBDS). MOs with different DBDS concentrations were aged at 150 °C for 5 days. Several parameters of the MO were measured, such as AC breakdown voltage, PDIV, apparent charge, average charge and PD repetition rate based on the needle-sphere, needle-plane and plane-plane electrode configurations. The AC breakdown voltage of aged MO displays a decrement pattern as the concentration of DBDS in the oil increases for all electrode configurations and gap distances. The average apparent charge of aged MO depicts an increment pattern in the presence of DBDS, whereas the PD repetition rate of aged MO displays variations of patterns for all electrode configurations. The PDIV of aged MOs shows an increment pattern at a 10 mm gap distance for all electrode configurations in the presence of DBDS. In contrast, the increment pattern of aged MOs is only observed for plane-plane electrode configuration at a 20 mm gap distance in the presence of DBDS. PDs occur predominantly at negative peak half-wave between the 3rd to 4th quadrants and are undetectable at positive half-wave in base and aged MO for all electrode configurations.